An improved 15N tracer approach to study denitrification and nitrogen turnover in soil incubations. (12th August 2016) - Scheer, Clemens; Meier, Rudolf; Brüggemann, Nicolas; Grace, Peter R.; Dannenmann, Michael
Abstract : Rationale: Denitrification (the reduction of oxidized forms of inorganic nitrogen (N) to N2 O and N2 ) from upland soils is considered to be the least well‐understood process in the global N cycle. The main reason for this lack of understanding is that the terminal product (N2 ) of denitrification is extremely difficult to measure against the large atmospheric background. Methods: We describe a system that combines the 15 N‐tracer technique with a 40‐fold reduced N2 (2% v/v) atmosphere in a fully automated incubation setup for direct quantification of N2 and N2 O emissions. The δ 15 N values of the emitted N2 and N2 O were determined using a custom‐built gas preparation unit that was connected to a DELTA V Plus isotope ratio mass spectrometer. The system was tested on a pasture soil from sub‐tropical Australia under different soil moisture conditions and combined with 15 N tracing in extractable soil N pools to establish a full N balance. Results: The method proved to be highly sensitive for detecting N2 (1.12 μg N h −1  kg −1 dry soil (ds)) and N2 O (0.36 μg N h −1  kg −1 ds) emissions. The main end product of denitrification in the investigated soil was N2 O for both water contents, with N2 accounting for only 3% to 13% of the total denitrification losses. Between 90 and 95% of the added 15 N fertiliser could be recovered in N gases and extractable soil N pools. Conclusions: The high and N2 O‐dominated denitrification rates found in this study are pointing at both the high ecological and the agronomic importance of denitrification in subtropical pasture soils. The new system allows for a direct and highly sensitive detection of N2 and N2 O fluxes from soils and may help to significantly improve our mechanistic understanding of N cycling and denitrification in terrestrial agro‐ecosystems. Copyright © 2016 John Wiley & Sons, Ltd.